Synthesis of noble metal nanomaterials with new crystal phases for electrocatalytic reaction - Wang, Jie (Nanyang Technological University, 2020)
To prepare noble metal nanomaterials with unconventional crystal phase is of extraordinary interest for the research of new features of noble metal nanomaterials towards a series of applications. Hence, the target of this thesis is to produce noble metal nanomaterials with unconventional crystal phase and then investigate their features in a range of catalytic applications.